Accumulation of microplastics in fish guts and gills from a large natural lake: Selective or non-selective?. (15th September 2022) - Yin, Xiaowei; Wu, Jiajun; Liu, Yunzhao; Chen, Xin; Xie, Chang; Liang, Yangyang; Li, Jing; Jiang, Zhongguan
Abstract: In recent years, microplastics (MPs) have become emerging contaminant causing widespread concern about their ecotoxicological effects. However, little is known regarding the accumulation of MPs in different tissues of fishes, especially for freshwater fishes in natural environments. In this study, MPs in guts and gills of 11 fish species from Lake Chao, China were examined to explore the accumulation differences and foraging preferences of MPs. In general, MPs in fish guts varied from 2.85 to 8.38 items/individual, while ranged from 3.06 to 8.90 items/individual in fish gills. In terms of characteristic composition (shape, color, size, and polymer type), our results demonstrate higher occurrence of fibrous, black, small sized (<1 mm), and polypropylene MPs. Meanwhile, MPs concentrations in fish guts differed significantly among various feeding groups, with none significant difference detected in fish gills. In addition, fish guts exhibit more distinct foraging preferences for specific featured MPs in contrast with fish gills. These results indicate selective MPs accumulation in fish guts whereas random MPs accumulation in fish gills. Fish gills, adhering MPs by non-selective water exchange, may be more related to the real-time MPs abundance in water. To some extent, fish gills may be employed as important instruments to reflect MPs contamination in aquatic environments. Influenced by diverse feeding behaviors such as visual cues and sensory systems, MPs accumulation in fish guts reflect intrinsic differences, thus making fish guts sensitive organ in monitoring MPs' ecological risk for their health. Highlights: Diverse microplastics (MPs) were detected in fish guts and gills from Lake Chao. Our study found selective and random MPs accumulation in fish guts and gills. Fish guts can be indicator organ to study their risk in exposing to MPs pollution. MPs in fish gills may reflect MPs contamination in aquatic environments.